Pengendalian Persediaan Bahan Baku Penolong Menggunakan Metode Economic Order Quantity di Industri Makanan Olahan - Mufti, Wahyu Fitrianda; Zulhamidi; Rusmin, Salman Alfarissi; Musdirwan (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2022)
CV. XYZ is a company engaged in food processing, it processes meat as the main raw material. Beef rollade is one of the products produced by CV. XYZ using "Fort Quarter" (FQ) beef as raw materials and auxiliary ingredients, i.e spices, eggs, onions, TVP (Texture Vegetable Protein) Red, and flour. TVP Red is an important auxiliary raw material in beef rollade production. A shortage of auxiliary materials for TVP Red during the production process will disrupt the process and if production continues, the product quality will decrease. Currently, the inventory policy carried out by CV. XYZ is to check the inventory of and auxiliary materials just before carrying out production activities so that if there is a shortage of auxiliary materials, new orders are made at that time. Therefore, the aim of this study is to determine the number of orders and the optimal frequency of ordering TVP Red using the EOQ method and determining the total cost of TVP Red inventory before and after using the EOQ method. Based on the results of calculations carried out using the EOQ, it can be concluded that the number of economical purchases of TVP Red is 1,007.6 Kg per order. With that number of purchases, the frequency of ordering by CV. XYZ is reduced to 13 times in one year. The difference in the frequency of these purchases is 25 times in one year. With purchase frequency of 13 times in one year, it can save the total inventory cost of Rp. 163.972,4.